The Star, 24 June 2008 - Ratner, Andrew (The New Straits Times Press (M) Bhd, 2008)
Print is having some issues at the moment, which may be like saying New Orleans took on some water. Insult fly, playground-style, about how long one published entity or another will be alive. Microsoft's CEO says no ink-on-paper newspapers or magazines by 2018; someone else says there'll be no Microsoft by then either.